Persons with a Mental Disorder as a Client of Social Work – Research Findings in the Czech Republic - Šuľová, Michaela (Technium Social Sciences Journal, 2025)
In social work, we see the client holistically, that is, in his complexity as a biological-psychological-social-spiritual being. His social problem often includes also a health aspect, or, other times, the health problem may be a trigger of the social problems. There is currently a growing number of people suffering from a mental disorder. Also in social services, there is a growing number of clients, who have a mental disorder, whereby this does not have to be their primary social diagnosis. Our goal was to analyze the social services primarily focused on people with mental disorders in the Czech Republic. To examined the process and determine the methods of social work with this target group. Identify social problems of this target group. We have conducted the research in qualitative methodology, where we have used semi-structure interview for data collection, open coding for analysis and the card sorting technique for evaluation. The research set consisted of 13 workers in social facilities primarily focused on people with mental disorders in the Czech Republic. According to our research findings there is a wide network of social services aimed at helping people with mental disorders in the Czech Republic, whereby many operate on the principle of multidisciplinarity. As part of social interventions, the social workers use a broad spectrum of methods and activities, which help the clients improve their problematic situation. The social problems of people with mental disorders include primarily employment, housing and relationships.